2020
DOI: 10.1038/s41598-020-71656-w
|View full text |Cite
|
Sign up to set email alerts
|

Recent atmospheric drying in Siberia is not unprecedented over the last 1,500 years

Abstract: Newly developed millennial δ13C larch tree-ring chronology from Siberia allows reconstruction of summer (July) vapor pressure deficit (VPD) changes in a temperature-limited environment. VPD increased recently, but does not yet exceed the maximum values reconstructed during the Medieval Warm Anomaly. The most humid conditions in the Siberian North were recorded in the Early Medieval Period and during the Little Ice Age. Increasing VPD under elevated air temperature affects the hydrology of these sensitive ecosy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 57 publications
2
24
0
Order By: Relevance
“…indicates that the modern, increasing level of drought stress is not yet unprecedented, being surpassed by a high vapour pressure deficit during the MCA (Churakova Sidorova et al, 2020). This is similar to trends observed in the fire reconstruction at Lake Khamra.…”
Section: Climatesupporting
confidence: 78%
See 1 more Smart Citation
“…indicates that the modern, increasing level of drought stress is not yet unprecedented, being surpassed by a high vapour pressure deficit during the MCA (Churakova Sidorova et al, 2020). This is similar to trends observed in the fire reconstruction at Lake Khamra.…”
Section: Climatesupporting
confidence: 78%
“…Although it has been demonstrated that the timing and extent of these climatic phases are heterogeneous (Guiot et al, 2010), evidence for their occurrence in Siberia is seen in other proxy studies (Churakova Sidorova et al, 2020;Kharuk et al, 2010;Osborn and Briffa, 2006), albeit less pronounced when it comes to vegetation response in the West Siberian Lowland (Philben et al, 2014). Neukom et al (2019) show how these climatic periods arising from averaged reconstructions at many individual study sites are not spatially or temporally coherent on the global scale, and conclude that environmental reconstructions "should not be forced to fit into global narratives or epochs".…”
Section: Climatementioning
confidence: 97%
“…Macroscopic charcoal particles in sediment archives, derived from biomass burning, are commonly used as a proxy for fire activity (e.g. Clark, 1988;Conedera et al, 2009;Remy et al, 2018;Whitlock and Larsen, 2001). Charcoal records are an important tool for tracking past changes in fire regimes and searching for underlying causes and effects, from local to global scales (Marlon et al, 2008(Marlon et al, , 2013Power et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…In the Siberian north, the Medieval Warm Period during the tenth century was warmer but wetter compared to the recent period derived from our results. This is opposite to the northeastern part of Siberia, where recent atmospheric drought events significantly increased compared to the past 21 . Earlier warming in springs lead to earlier snowmelt 1 , developing a water shortage for trees by increasing the evapotranspiration in the Siberian subarctic 21 .…”
Section: Discussionmentioning
confidence: 59%
“…Tree-ring width chronologies from the Siberian subarctic record mainly June-July air temperature signal 11 13 . The variation of stable carbon isotopes in tree rings can provide complementary information about changes in precipitation 15 – 19 , sunshine duration 20 , vapor pressure deficit 21 and cloud cover 22 , while oxygen isotopes can record information about atmospheric circulation patterns 16 , 23 27 .…”
Section: Introductionmentioning
confidence: 99%